Dynamics of the underground economy in border areas: A case study of Indonesia-Timor Leste - Nalle, Frederic Winston; Suman, Agus; Kaluge, David; Ekawati, Marlina (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
The underground economy in border regions represents a complex phenomenon shaped by regulatory gaps, limited access to formal economic systems, and high transaction costs in legal trade. This study analyzes the dynamics of informal cross-border trade along the Indonesia–Timor-Leste border, focusing on North Central Timor (TTU) Regency and the Oecusse Enclave. Employing a qualitative descriptive approach, the research draws on field observations, semi-structured interviews, and thematic analysis to demonstrate that underground economic activities function not only as a survival strategy but also as an informally institutionalized, socially organized economic ecosystem. The findings reveal that price disparities, weak supervision, and limited institutional capacity collectively drive communities’ dependence on illicit trade. A comparative analysis of similar cases from international border regions highlights the need for policy responses tailored to local contexts. The study recommends strengthening bilateral cooperation, adopting surveillance technologies suited to regional capacities, and implementing community-based economic empowerment programs to facilitate the transition toward an inclusive and sustainable formal economy.